Estudio de prefactibilidad para la instalación de una planta productora de aceite de tarwi (Lupinus mutabilis) - Chillitupa Arredondo, Carmen Patricia (2023)
This research study seeks to determine the economic, technological, social and market feasibility for the installation of a tarwi oil production plant. The target market for the product is people who have a healthy lifestyle, who live in Metropolitan Lima and reside in zones 6 and 7. In Chapter I, the current problem is analyzed, the objectives and general aspects of the research are presented. In Chapter II, it establishes the characteristics and uses of the product, then determines the potential demand and the apparent internal demand for edible oils in Peru, and finally, performs a market study to determine the demand for the project, which for the year 2027 is 28 561 liters or 57 123 bottles. In Chapter III, different factors are evaluated to determine the macro-location and micro-location of the production plant, where it is determined which optimal location is in Lurín district, within the Lima Metropolitan region. In Chapter IV it is determined that the plant size is 57 123 bottles, and the actual capacity of the plant is 90 953 bottles. In Chapter V the production process is detailed, and it is determined that the raw material, supplies, and services are not limiting to carry out the project. In chapter VI the type and formation of the company are detailed. In Chapter VII it is determined that the total investment is 1 344 338 PEN , the VANE is 439 777 PEN and the VANF is 790 197 PEN; the TIRE is 20.76% and the TIRF is 33.44%. Likewise, it was determined that the recovery period is 3,23 years and finally the sensitivity analysis and the social evaluation of the project were carried out.